The Systematic Study on the Stability and Superconductivity of Y‐Mg‐H Compounds under High Pressure. Issue 3 (18th January 2022) - Song, Peng; Hou, Zhufeng; de Castro, Pedro Baptista; Nakano, Kousuke; Takano, Yoshihiko; Maezono, Ryo; Hongo, Kenta
Abstract: Structural stabilities of high‐pressure YMgH x phases ( x = 2 − 10, 12, 14 $x = 2-10, 12, 14$, and 16) and their superconductivities are investigated by employing evolutionary‐algorithm‐based crystal search combined with first‐principles calculations. For predicted candidate structures of YMgH x, the convex hull and phonon analyses reveal seven stable and two metastable phases. For all the predicted phases, superconducting transition temperatures ( T c ) are also predicted by using the McMillan formula. P 4 / m m m $P4/mmm$ ‐YMgH6 is found having T c = 76 $T_c = 76$ K at 300 GPa comparable to the boiling temperature of liquid nitrogen, and high‐ T c (≥77 K) being predicted for the H‐richer phases, P 4 / m m m $P4/mmm$ ‐YMgH8 (124 K at 300 GPa), C m m m $Cmmm$ ‐YMgH12 (152 K at 250 GPa), and F d 3 ¯ m $Fd\bar{3}m$ ‐YMgH12 (190 K at 200 GPa), which possess clathrate structures composed of H14, H18, H24, and H24 cages, respectively. To elucidate why the H‐rich phases attain high‐ T c, electronic and phonon band structures as well as electron–phonon coupling strength are analyzed based on Eliashberg spectral functions. The clathrate structures exhibit both a larger H‐driven electronic density of states at the Fermi level and a denser H‐driven phonon density of states, correlating with larger EPC constants. These structural and chemical bonding analyses reveal that the highest‐ T c phase F d 3 ¯ m $Fd\bar{3}m$ ‐YMgH12 has H4 units formed in the sodalite cage. Abstract : The high pressure phase diagram of Y‐Mg‐H system is determined by first‐principles structural search. The potential high‐temperature superconducting compounds among the Y‐Mg‐H system are discovered by first‐principles electron‐phonon calculations and McMillan formula. For instance, the Fd‐3m‐YMgH12 possesses a T c value of 190 K, which is the highest T c among the Y‐Mg‐H system.